Development of Mobile Game Application : “Saving Endangered Flora” - Tan, Siao Tian; Suriawati Suparjoh (Applied Information Technology And Computer Science, 2022)
“Saving Endangered Flora” is an educational game for users to gain knowledge about endangered flora. Research on existing mobile games found issues related to poor interface design, limited content explanation about endangered flora, and sound problems. The main objective of the project is to design a mobile game-based learning which emphasis about endangered flora. Game Development Life Cycle (GDLC) model used as the methodology basis and Unity as the development tool. C# language is used to codes the game mechanisms. The design part well-supported by Adobe Illustrator, which creates the assets of the mobile game. A total of 10 children participated in the Beta Testing. In terms of learning outcome acquisition, 80% of respondents agreed that they learn about endangered flora from this game, and 70% of respondents agreed that they know the reason for the decrease of endangered flora. Most of the respondents give positive feedback in interface design, game instructions and overall gameplay experience. Overall, this “Saving Endangered Flora” game had a good outcome and is well accepted by the target users.